Produktivitas Karkas Domba Garut Jantan pada Pemberian Jenis Pakan dan Waktu yang Berbeda - Aslimah, S.; Yamin, M.; Astuti, D. A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2014)
Garut sheep (GS) is one of important commodity in Indonesia.   The aims of this  research were to evaluate the Effect of mungbean sprouts waste and different time feeding management(morning,evening)on the carcass productivity  in garut  rams.In this experiment  12 male  garut were used,  aged  6-7  months, weighed  16.76 ± 2.09 kg (CV = 8.01 %).They  were arranged  into  a completely  randomized design  with  factorial  2x2 and 3 replications.Feed ration was first factor observed (R1=40% mix grass+60% concentrate and R2=     40%mungbean sprouts  waste + 60% concentrate) and            second  factor was feeding  time  management,  morning (M)     and evening (E). The data were analyzed by analysis of              variance. The results showed that there was  no interaction between two main factors (P<0.05). GS with R2 treatment have slaughter weight, carcass weight and carcass fat  which higher     than R1. Feeding GS  in the  evening  increased  the             proportion  of  meat.  The percentages of carcass were 39.07 %  inR1M;37.18%in  R1E;41.99% in R2M and 42.46%  in R2E.  Feeding GS with mungbean sprouts increased average daily gain around 141.29 gram head/day.